2019
DOI: 10.3390/buildings9030069
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Human Safety Assessment (PHSA) for the Improvement of the Behavioral Aspects of Safety Climate in the Construction Industry

Abstract: Occupational safety in the construction industry still represents a relevant problem at a global level. In fact, the complexity of working activities in this sector requires a comprehensive approach that goes beyond normative compliance to guarantee safer working conditions. In particular, empirical research on the factors influencing the unsafe behavior of workers needs to be augmented. Thus, the relationship between human factors and safety management issues following a bottom-up approach was investigated. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 79 publications
1
33
0
Order By: Relevance
“…For example, Ghasemi et al [59] used SHERPA to identify human error types in control units of the petrochemical industry, while Harris et al [51] used this tool to analyze aircraft pilots, and suggested that that error types such as "actions" and "checks" are particularly suited to the analysis of these work tasks. Other examples of the SHERPA application can be found in the analysis of heavy machinery operators in the construction sector [34], as well as in the analysis of the task of administering drugs to hospital patients [35]. Other studies have focused on extensions of the SHERPA method [53].…”
Section: Systematic Human Error Reduction and Prediction Approach (Shmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ghasemi et al [59] used SHERPA to identify human error types in control units of the petrochemical industry, while Harris et al [51] used this tool to analyze aircraft pilots, and suggested that that error types such as "actions" and "checks" are particularly suited to the analysis of these work tasks. Other examples of the SHERPA application can be found in the analysis of heavy machinery operators in the construction sector [34], as well as in the analysis of the task of administering drugs to hospital patients [35]. Other studies have focused on extensions of the SHERPA method [53].…”
Section: Systematic Human Error Reduction and Prediction Approach (Shmentioning
confidence: 99%
“…In fact, further studies on behavioral factors in pesticide use, including risk perception, are of major importance for effective risk management [32]. To address these issues, a human-centered approach is needed with the aim of investigating the different phases that characterize the work activities [33,34]. As argued by several authors in different fields, human error analysis can allow a better understanding of how human interaction with work tasks might lead to accidents and incidents [35][36][37], since normative approaches do not properly consider the characteristics of the work processes [38].…”
mentioning
confidence: 99%
“…This accomplishes the research clues by Cividino et al [36], who pointed out the low perception and awareness of safety issue by the workers in the agricultural sector. Accordingly, as demonstrated also in other fields [45], [46], safety perception and climate in small working contexts need to be augmented, in order to reduce the number of accidents.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…BBS is deemed to be an effective approach to further prevent oil industry accidents. BBS has been successfully applied in a wide range of areas such as health care and hospitals [17,18], transportation [19][20][21], manufacturing [22], and construction [23][24][25]. These successful applications illustrated the effectiveness of the BBS approach for identifying potentially risky or unsafe behaviors [26].…”
Section: Introductionmentioning
confidence: 99%